DECONSTRUCTION PERSPECTIVE TOWARDS THE CHARACTERS IN CHRISTINA ROSSETTI’S “GOBLIN MARKET” POEM - M. Bahri Arifin; Singgih Daru Kuncara; Fatimah M. (Prosiding Seminar Nasional Bahasa, Sastra, dan Seni (Sesanti), 2019)
Jacques Derrida was the French philosopher and a founding father of deconstruction theory. He challenged the logo-centric Western tradition of the metaphysics of presence. His theory of deconstruction attacked the presuppositions of meaning in a literary works that literary text has conventional or fixed meaning. Deconstruction could bring a new meaning and perspective to Christina Rossetti's poem "Goblin Market". This research aimed to scrutinize the different facets towards the characters in Rosetti’s poem Goblin Market from Derrida deconstructive theory. The researcher used descriptive qualitative method and objective approach in examining the text of the poem. The result of the study showed a new portrait of the personages of the poem after retracing the meaning of the text. The researcher analysed some characters of the poem namely, Lizzie and Laura as the representation of female characters in the poem, and the queer creatures called “the goblin” characters that were addressed to male characters. In this research, the researcher found some binary oppositions through deconstruction analysis of the poem includes, the idea of brotherhood vs. sisterhood, humanity vs. others, good character vs. evil character.